Efficacy and safety of low-dose SoluMatrix meloxicam in the treatment of osteoarthritis pain: a 12-week, phase 3 study. (2nd December 2015) - Altman, Roy; Hochberg, Marc; Gibofsky, Allan; Jaros, Mark; Young, Clarence
Abstract: Objective: Nonsteroidal anti-inflammatory drugs (NSAIDs) such as meloxicam are commonly used to treat osteoarthritis (OA) but are associated with potentially serious dose-related adverse events (AEs). SoluMatrix * meloxicam has been developed with the goal of enabling effective treatment at low doses. This phase 3 study evaluated the efficacy and safety of low-dose SoluMatrix meloxicam capsules 5 mg and 10 mg administered once daily for 12 weeks in patients with OA-related pain. Research design and methods: This randomized, double-blind study enrolled patients ≥40 years of age with confirmed hip or knee OA (Kellgren–Lawrence grade II–III) who were chronic users of NSAIDs and/or acetaminophen for OA pain and had Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscale mean scores ≥40 mm. Eligible patients experienced an OA pain flare (defined as a ≥15 mm increase in the WOMAC pain subscale score) following discontinuation of NSAIDs/acetaminophen. Patients were randomized to receive once-daily SoluMatrix meloxicam 5 mg or 10 mg, or placebo for 12 weeks. ClinicalTrials.gov identifier: NCT01787188. Main outcome measures: The primary outcome measure was the mean change from baseline in WOMAC pain subscale score at week 12. Results: Low-dose SoluMatrix meloxicam 5 mg (−36.52 [2.49]; P  = 0.0005) and 10 mg (−34.41 [2.68]; P  = 0.0059) once-daily treatment significantly reduced the mean (standard error) WOMAC pain subscale score from baseline at week 12 compared with placebo (−25.68 [2.64]). Patients treated with SoluMatrix meloxicam 5 mg or 10 mg reported significantly greater improvements in total WOMAC score and in WOMAC stiffness and function subscale scores at 12 weeks compared with placebo. The most common AEs in the combined low-dose SoluMatrix meloxicam group were headache, diarrhea, nausea, osteoarthritis, and urinary tract infection. Conclusions: Low-dose SoluMatrix meloxicam may have a potential role as a new therapeutic option for the management of OA-related pain.